Impact of clustering in different layers on performance for ad hoc wireless networks - Trajanov, Dimitar; Filiposka, Sonja; Grnarov, Aksenti (My University, 2003)
The main application of wireless mobile ad hoc networks is to offer services for situations wherein groups of people come together and share information. The groups of people that use the ad hoc network form some kind of real social network. Thus, real social networks exhibit clustering, the tendency of two individuals who share a mutual friend to be friends themselves. In this paper impact of clustering on performance of ad hoc network is investigated. It is shown that clustering has a big influence on the performance. One can conclude that the only way to obtain satisfying performances in large ad hoc network is clustering on physical and logical layer.
Keywords: ad hoc network, clustering, performance, application layer, clustering performance factor